2011
DOI: 10.1074/mcp.m111.010538
|View full text |Cite
|
Sign up to set email alerts
|

Independent Analysis of the Flagellum Surface and Matrix Proteomes Provides Insight into Flagellum Signaling in Mammalian-infectious Trypanosoma brucei

Abstract: The flagellum of African trypanosomes is an essential and multifunctional organelle that functions in motility, cell morphogenesis, and host-parasite interaction. Previous studies of the trypanosome flagellum have been limited by the inability to purify flagella without first removing the flagellar membrane. This limitation is particularly relevant in the context of studying flagellum signaling, as signaling requires surface-exposed proteins in the flagellar membrane and soluble signaling proteins in the flage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
201
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(222 citation statements)
references
References 111 publications
(134 reference statements)
9
201
1
9
Order By: Relevance
“…The TbNMT knockdown resulted in a shift of electrophoretic mobility of POMP39 and a concomitant change of localization, whereas the putative palmitoylation was experimentally addressed in a previous study (Emmer et al, 2011). In line with the global proteomics studies mentioned above Panigrahi et al, 2009;Oberholzer et al, 2011), we show that a fraction of the protein localizes to the flagellum, whereas another fraction is stably associated with the MOM.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The TbNMT knockdown resulted in a shift of electrophoretic mobility of POMP39 and a concomitant change of localization, whereas the putative palmitoylation was experimentally addressed in a previous study (Emmer et al, 2011). In line with the global proteomics studies mentioned above Panigrahi et al, 2009;Oberholzer et al, 2011), we show that a fraction of the protein localizes to the flagellum, whereas another fraction is stably associated with the MOM.…”
Section: Discussionsupporting
confidence: 75%
“…60% identity) was in our proteomics study never found in the mitochondrial fraction and had the relative maximal intensity in the crude ER fraction (Niemann et al, 2013). Furthermore, it was not detected in the flagellar proteome (Oberholzer et al, 2011).…”
Section: Pomp39 Localizes To Mitochondria and Flagellacontrasting
confidence: 47%
See 3 more Smart Citations